Improving Students’ A Bility In Speaking And Writing Descriptive Text By Using Think, Talk, Write (TTW) Strategy A Classroom Action Research at the Tenth Grade Students of - Dzikroh Nurdinie (Metakognisi, 2020)
The aims of this research are : (1) To find out the process of improving students’ ability in speaking and writing descriptive text by using Think-Talk-Write (TTW) strategy at the tenth grade students of SMK Babunnajah. (2) To find out the result of improving students’ ability in speaking and writing descriptive text by using Think-Talk-Write (TTW) strategy at the tenth grade students of SMK Babunnajah. This research is qualitative by implementing Classroom Action Research (CAR). The research was conducted at SMK Babunnajah in Mei until June 2019. The subjects of this research were the tenth grade students of SMK Babunnajah. It consists of 20 students. This classroom action research was conducted in two cycles. Each cycle consisted of four steps: plan, action, observation, and reflection. The data were collected from qualitative and quantitative. The research findings show that the mean of writing score in pre-test was 48.25, the mean of writing score in post-test cycle I was 66.25, and the mean of writing score in post-test cycle II was 77.25. While, the mean of speaking score in pre-test was 56, the mean of speaking score in post-test cycle I was 70,8 and the mean of speaking score in post-test cycle II was 81.2. It means that post-test 1 was higher than pre-test and post-test 2 were higher than post-test 1. It can be concluded that Think-Talk-Write Strategy can improve students’ writing and speaking ability in descriptive text.